KxNiy[Fe(CN)6].xH2O Prussian blue analogue: A study of size effect on the structural, optical and magnetic propertiecs - Phu, Phung Kim; Giang, Trinh Ngoc; Minh, Nguyen Van (Communications in Physics, 2008)
Recently, striking effects of light irradiation on the magnetic state were reported for Prussian blue (PB) analogues AxCoy[Fe(CN)6] (A = Na, K, Rb, Cs). The physical and optical properties of these compounds are dependent on the size of the particles of the measured samples. However, there have been few reports on the formation of nano-sized particles of the material and the effect of size of the particles on the properties of the compounds. In this report, we present a novel synthesis method of the KxNiy[Fe(CN)6] PB nano-particles and investigate the effect of particlesize on the properties of the Prussian blue analog KxNiy[Fe(CN)6] by analysising the results of the X-ray diffraction (XRD), scanning electron microscopy (SEM), UV-vis absorption and magnetization measurements of the compounds. Keywords: Prussian Blue, nanoparticle, size effect, magnetic property